(untitled) (Latakia University Journal -Basic Sciences Series, 2020)
The electrostatic field lines pass the dielectrics in intermittent form , but they cannot pass the metals , but one of current research shown ,that the electrostatic field lines pass the metals also, and they travel through it by velocity higher than light velocity. Follows it ,that the metals have a very high relative permittivity compared with relative permittivity of dielectrics . In this research , we have explained how and when the metals have relative permittivity semiconductors, we have also calculated their values for five different metals , we calculated also the apparent velocity of electrostatic field lines within some metals , and the ligated depths of electric charges within it, we have also explained the wrong by calculating the velocity of electric field signal in metals , that lead to contradiction with theory of relativity.